Free basics : fragmenting the internet or digital inclusion - Mukherjee, Kajari (London : Neilson Journals Publishing, 2018)
Zero Rating (ZR) allowed conditional internet access to those who otherwise could not afford it. Free Basics by Facebook was a ZR plan, introduced in India in February 2015. Facebook argued that Free Basics allowed the poor free access to useful sites. With two-thirds of the world's population offline, Facebook made a compelling case for digital inclusion. The argument against Free Basics was its limited offering which did not reflect the richness of the open web and the birth of a digital divide. The Telecom Regulatory Authority of India (TRAI) passed a consulting paper in December 2015 on differential pricing. This produced up to 2.4 million comments. Post the consultation process, TRAI stopped conditional access to internet in February 2016. This case study reflects the world-wide contentious issue of differential pricing for data access with the debate centered on (a) internet as a public good, (b) net neutrality, (c) conditional but free access to limited sites versus public internet with unfettered access to all sites, (d) intrinsic value of connectivity versus its transformative potential, and (e) challenges of developing public policies where beneficiary is not only the target but also an agent in co-creation; and if the intended beneficiaries' voice gets heard in such debates.
Originally Published In Mukherjee, K. (2018). Free Basics: Fragmenting the Internet or Digital Inclusion. Journal of International Business Education, 13(1), 349-362. JIBE13-0CS6.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Internet access -- India -- Case studies